Increased suicide risk among patients oophorectomized following benign conditions and its association with comorbidities. (2nd April 2020) - Chiu, Li-Wei; Lin, Kent Yu-Hsien; Chang, Cherry Yin-Yi; Lin, Wu-Chou; Wan, Lei
Abstract: Objective: To evaluate the suicide rate among patients oophorectomized for benign conditions and its association with confounding comorbidities. Method: We conducted a population-based, retrospective cohort study of women aged ≥20 years that underwent oophorectomy including unilateral or bilateral in laparotomy or laparoscopy for benign conditions during 2000–2013. A total of 145, 588 oophorectomized and 582, 352 non-oophorectomized women were included with an average follow-up time of 7 years. The comorbidities assessed were hypertension (HTN), diabetes mellitus, hyperlipidemia, stroke, chronic obstructive pulmonary disease (COPD), chronic liver disease and cirrhosis, chronic kidney disease and anxiety disorder. Result: The overall suicide rate was significantly higher in the oophorectomized group. The rate among oophorectomized patients of 20–49 years was significantly greater than in non-oophorectomized patients of the same age group. Hypertension, COPD, anxiety disorder and chronic liver disease and cirrhosis were associated with a significantly higher suicide rate in oophorectomized women. A significant increase in suicide incidence was observed in patients with <6 years' follow-up. Conclusion: A significant increase in suicide rate among oophorectomized women aged 20–49 years was found. The decision to perform oophorectomy should be made cautiously, especially in patients with hypertension, COPD, chronic liver disease and cirrhosis or anxiety disorder. Patients should be followed for at least 6 years postoperatively since the suicide rate is significantly higher in this period.